Micropropagation of Dendrobium sp. via somatic embryogenesis culture - Tuong Thu, Bui Thi; Minh, Tran Van (Academia Journal of Biology, 2012)
Protocorm like bodies were used as planting materials. PLBs were cut into slices and placed on the medium for callus initiated. Callus was initiated on the medium MS + CW (30%) + 2.4D (0.5 mg/l). Callus proliferates on the medium MS + CW (10%) supplemented with NAA (0.5 mg/l) + 2.4D (0.1 mg/l). Callus was regenerated on the medium MS + (10%) supplemented with + NAA (0.1 mg/l) + BA (0.1 mg/l). Somatic cell suspension was initiated on MS + 2.4D (0.5 mg/l) and proliferated on the medium MS + CW (10%) supplemented was NAA (0.5 mg/l) + 2.4D (0.1 mg/l). Somatic cell suspension was differentiated to embryogenic cell suspension on the medium MS +  CW (10%) supplemented with NAA (0.1 mg/l) + BA (0.1 mg/l). Embryogenic cell suspension was plating and regeneration on the medium MS + CW (10%) + NAA (0.1 mg/l) + BA (0.1 mg/l).